Wireless all-in-one desk reference for dummies - Carter, Todd W. (Indianapolis, IN : Wiley Pub., Inc., 2005)
Comprehensively covers Wi-Fi networks, handhelds, and entertainment in ten mini-books, shows how to link PDAs, laptops, TiVo and sound systems to a wireless network, and guides the user through setting up a home wireless network
Includes index
Keywords: Wireless communication systems; Computer networks